Good Wild Harmonic Bundles and Good Filtered Higgs Bundles - Mochizuki, Takuro (Symmetry, Integrability and Geometry: Methods and Applications, 2021)
We prove the Kobayashi-Hitchin correspondence between good wild harmonic bundles and polystable good filtered λ-flat bundles satisfying a vanishing condition. We also study the correspondence for good wild harmonic bundles with the homogeneity with respect to a group action, which is expected to provide another way to construct Frobenius manifolds.